Adab and modernity : a "civilising" process? (sixteenth--twenty-first century) - Mayeur-Jaouen, Catherine, (Islamic Literatures: Texts and Studies;, 2020)
Adab is a concept situated at the heart of Arabic and Islamic civilisation. Adab is etiquette, ethics, and literature. It is also a creative synthesis, a relationship within a configuration. What became of it, towards modernity ? The question of the "civilising process" (Norbert Elias) helps us reflect on this story. During the modern period, maintaining one's identity while entering into what was termed "civilisation" ( al-tamaddun ) soon became a leitmotiv . A debate on what was or what should be culture, ethics, and norms in Middle Eastern societies accompanied this evolution. The resilient notion of adab has been in competition with the Salafist focus on mores ( akhlāq ). Still, humanism, poetry, and transgression are constants in the history of adab . Contributors: Francesca Bellino, Elisabetta Benigni, Michel Boivin, Olivier Bouquet, Francesco Chiabotti, Stéphane Dudoignon, Anne-Laure Dupont, Stephan Guth, Albrecht Hofheinz, Katharina Ivanyi, Felix Konrad, Corinne Lefevre, Cathérine Mayeur-Jaouen, Astrid Meier, Nabil Mouline, Samuela Pagani, Luca Patrizi, Stefan Reichmuth, Iris Seri-Hersch, Chantal Verdeil, Anne-Sophie Vivier-Muresan.